2008
DOI: 10.1148/radiol.2461061907
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Metastasis in Non–Small Cell Lung Cancer: Accuracy of 3.0-T MR Imaging

Abstract: Morphologic details of lymph nodes on T2-weighted triple-inversion black-blood fast spin-echo MR images are significant for detection of mediastinal or hilar nodal metastasis at 3.0-T MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…However, this sizebased characterization of lymph node metastasis frequently leads to misdiagnosis as metastatic lymph nodes may be of normal size, whereas nonmetastatic lymph nodes may become abnormally enlarged due to reactive swelling (defined pathologically as reactive lymphadenopathy; ref. 9). Recently, Zhang and colleagues (10) have reported that both diffusion-weighted and superparamagnetic iron oxide-enhanced MRI can distinguish tumor metastatic lymph nodes from reactive lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this sizebased characterization of lymph node metastasis frequently leads to misdiagnosis as metastatic lymph nodes may be of normal size, whereas nonmetastatic lymph nodes may become abnormally enlarged due to reactive swelling (defined pathologically as reactive lymphadenopathy; ref. 9). Recently, Zhang and colleagues (10) have reported that both diffusion-weighted and superparamagnetic iron oxide-enhanced MRI can distinguish tumor metastatic lymph nodes from reactive lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Eccentric cortical thickening and obliteration of the fatty hilum are features suggestive of a malignant node. 48 Conventional CT has a low sensitivity of 41%-68% and a specificity of 43%-97% in the detection of mediastinal nodal metastasis. 48,49 With MRI, the SI of malignant lymph nodes is higher than that of benign ones on T1W and T2W sequences.…”
Section: Staging Of Lung Cancermentioning
confidence: 99%
“…First, T2-weighted imaging played a role in screening for presumed metastatic lymph nodes and in facilitating anatomical correlation with the PET/CT. The nodes satisfying both high signal intensity and malignant morphological features on T2-weighted imaging were considered metastatic lymph nodes [18]. Second, malignant-looking nodes on T2-weighted imaging were evaluated on DWI.…”
Section: Combined Mri and Pet/ctmentioning
confidence: 99%
“…Some recent studies have reported that various magnetic resonance imaging (MRI) techniques can be useful for detecting and excluding nodal metastasis [15][16][17][18][19]. On T2-weighted triple-inversion black-blood fast spin-echo MRI, the morphological details of lymph nodes appear to be important for detecting nodal metastasis with high specificity and accuracy [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation